Effects of early childhood lead exposure on academic performance and behaviour of school age children. Issue 11 (21st September 2009) - Chandramouli, K; Steer, C D; Ellis, M; Emond, A M
Abstract : Aim: To determine whether early lead exposure at levels below 10 μg/dl has an impact on educational and behavioural outcomes at school. Methods: Venous samples were taken from a subgroup of the Avon Longitudinal Study of Parents and Children (ALSPAC) attending a research clinic at 30 months of age (n = 582), and lead levels were measured by atomic absorption spectrometry. Developmental, behavioural and standardised educational outcomes (Standard Assessment Tests, SATs) were collected on these children at age 7–8 years. In the analysis, blood lead concentration was investigated both as a continuous covariate and as a categorical variable. Results: 488 cases (84%) had complete data on confounders and outcomes. After adjustment for confounders and using a log dose–response model for lead concentration, blood lead levels showed significant associations with reading, writing and spelling grades on SATs, and antisocial behaviour. A doubling in lead concentration was associated with a 0.3 point (95% CI −0.5 to −0.1) decline in SATs grades. Treating lead levels categorically, with the reference group 0–2 μg/dl, no effects on outcomes were apparent at 2–5 μg/dl, but levels of 5–10 μg/dl were associated with a reduction in scores for reading (OR 0.51, p = 0.006) and writing (OR 0.49, p = 0.003). Lead levels >10 μg/dl were also associated with increased scores for antisocial behaviour (OR 2.9, p = 0.040) and hyperactivity (OR 2.82, p = 0.034). Conclusions: Exposure to lead early in childhood has effects on subsequent educational attainment, even at blood levels below 10 μg/dl. These data suggest that the threshold for clinical concern should be reduced to 5 μg/dl.